Study of ferromagnetic nanoparticles effect on tribotechnical lubricating characteristics - Elena Gennadyevna Zadoshenko; Victoria Eduardovna Burlakova (Advanced Engineering Research)
The research objective is to study tribological properties of the lubricating compositions based on the Castrol oil and ZIATIM -201 plastic lubricant modified by the ferromagnetic nanosuspension. A qualitative X-ray phase analysis by the diffractometry method is conducted on the ARL X´TRA computerized system to specify the compound of the synthesized ferromagnetic nanoparticles. An aqueous suspension of ferromagnetic nanoparticles is studied on CPS Disk Centrifuge Model DC24000 to determine the particle sizes. The investigation has been conducted by determining the tribological characteristics using four-ball machine. The preparation of lubricating compositions based on a number of sequence operations - ferromagnetic particles synthesis, their stabilization, and paste concentrate preparation - is described. On the basis of the X-ray data, it is found that the ferromagnetic particles composition corresponds to FeFe2 O4 magnetite. The sedimentation analytical data processing has shown the polydisperse nature of the derived magnetite nanoparticles. Based on the tribological studies, the antiwear properties are evaluated in wear scar diameter, the load wear index value is calculated, and the bearing capacity of the lubricant according to the welding load and critical load for the lubricants under study is identified. Thus, it is found that the lubricant compositions with magnetite additives based on ZIATIM -201 plastic lubricant and Castrol oil with magnetite content of 0.1% wt. offer high antiwelding and antiwear properties. Increase in the magnetite content in lubricants leads to the degradation of their antiwear properties.